Champion of the titan games - Mull, Brandon, 1974- (Mull, Brandon, 1974- Dragonwatch (Series), 2020)
The war against dragons intensifies. Will Kendra and Seth find the help they desperately need from the Giant Queen? This fourth book in a five-book series leaves the underwater dragon preserve of Crescent Lagoon for a gladiator-style arena at Titan Valley, the magical realm of towering giants and enslaved dragons. Our two young heroes have never felt so small or faced a challenge so . . . giant!